GEN ALPHA DI BANGKU SD: ANALISIS LITERATUR TENTANG PERGESERAN KARAKTER DAN LITERASI NILAI DI ABAD 21 - Arsanda Wikan Dinata; Adzra Aunatulah Salsabila; Shofiatul Muawanah; Adhistya Putri; Raccel Nadya Carisma Putri; Delia Indrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Generation Alpha in elementary schools indicates a significant shift in character and value literacy, driven by digital technology and the complex dynamics of the 21st century. This study aims to analyze student character changes and the transformation of value literacy through a comprehensive literature review. The method employed is a systematic literature study of relevant journals, books, and research reports from the last decade. Analysis reveals that while Generation Alpha is highly tech-adaptive, creative, and efficient in accessing information, they face challenges in discipline, social empathy, learning resilience, and self-regulation regarding technology use. Furthermore, value literacy has shifted from conventional forms toward more contextual, flexible, and digital-based values. This study concludes that a synergistic role between schools, teachers, and families is essential to balance character education with technology. Recommendations include strengthening adaptive curricula and collaborative learning strategies to develop holistic, critical, and competitive students for the future.